2013
DOI: 10.1161/circheartfailure.112.000255
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of α-1-Antichymotrypsin by MicroRNA-137 in Chronic Heart Failure and Mechanical Support

Abstract: There is substantial interest in applying proteomics to obtain better understanding of disease processes and to develop new biomarkers for diagnosis and early detection of cardiovascular diseases. 5,6 The purpose of the present study was to investigate proteomic changes in reverse remodeling during LVAD support. Because the degree of reverse remodeling is more pronounced in patients with nonischemic dilated cardiomyopathy (DCM), 7 we focused on this subset of patients. Recently, we found that levels of α-1-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…Consequently, novel biomarkers are currently under intensive investigation and may be of help to improve the prognostication and clinical outcome of HF patients. Recently, we proposed a role of the acute-phase protein alpha-1-antichymotrypsin (ACT; also known as SERPINA3) in reverse remodelling [10]. Our previous data demonstrated that high ACT plasma and myocardial levels in HF decrease during mechanical support.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, novel biomarkers are currently under intensive investigation and may be of help to improve the prognostication and clinical outcome of HF patients. Recently, we proposed a role of the acute-phase protein alpha-1-antichymotrypsin (ACT; also known as SERPINA3) in reverse remodelling [10]. Our previous data demonstrated that high ACT plasma and myocardial levels in HF decrease during mechanical support.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, our results show a significant increase in miR-378 and miR-378* in post pf-LVAD, indicating that increased expression levels of these miRs contribute to better cardiac function and therefore positive cardiac remodeling. Furthermore, we have very recently shown that miR-137 is implicated in reverse remodeling during cf-LVAD support by directly regulating alpha-1-antichymotrypsin, a potential new biomarker of HF [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are small, non-coding RNAs that bind mRNAs at their 3’-untranslated regions, stimulating mRNA degradation or inhibiting protein translation [ 22 ]. MiRs are important hallmarks for recovery or deterioration and might be used as a therapeutic target in HF [ 23 25 ]. Therefore, delineating their role in posttranscriptional gene regulation offers new insight into the mechanisms how the heart adapts to mechanical support.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression reduced interstitial fibrosis and heart failure in postmyocardial infarction rats miR-133 63 Collagen type 1 alpha 1 mRNA In Ang II dependent hypertension in rats, downregulation of miR-133 increases collagen type I alpha 1 production by myocytes in mice miR-137 64 Alpha-1-antichymotrypsin (ACT) miR-137 expression varied inversely with ACT mRNA in human cardiomyocytes and stromal cells miR-212/132 family 65 Fox03 transcription factor (antihypertrophic via calcineurin signaling suppression, also pro-autophagic via atrogin-1)…”
Section: Small Interfering Rnasmentioning
confidence: 99%